Естрадно-джазове вокальне виконавство як предмет сучасних музикознавчих досліджень в Україні - Корольчук, Ольга Леонідівна; Korolchuk, Olha L.; Чепелюк, Василь Адамович; Chepeliuk, Vasyl A. (Рівненський державний гуманітарний університет, 2017)
Здійснено огляд дисертаційних праць українського музикознавства, предметом дослідження яких є ті чи інші проблеми, пов’язані з естрадно-джазовим вокальним виконавством. Це праці В. Олендарьова, В. Романка, О. Воропаєвої, З. Рось, В. Тормахової, Н. Дрожжиної та деякі педагогічні дослідження. Перший аспект указаних робіт, акцентований у статті, є історичним, а саме – джаз як явище радянського (В. Олендарьов) та українського (В. Романко) мистецтва. Серед інших проблем джазового виконавства, що піднімалися в останнє 25-річчя – феномен джаззінгу, фестивальний процес та ін. У сфері естрадного вокального мистецтва вирізнено проблеми взаємодії з фольклором, вокальне інтонування тощо.

The aim of this paper is to review the dissertation works on the Ukrainian musicology, the subject of which is the problems related to the pop-jazz vocal. The research studies of such scientists as V. Olendarov, V. Romanko, O. Voropaieva, Z. Ros, V. Tormakhova, N. Drozhzhyna and some pedagogical problems are investigated. Research methodology. The main works on the Ukrainian musicology of the last twenty five years in the period of the state independence are analysed. The researches about pop and jazz, and pedagogical works are distinguished. Results. The modern development of the Ukrainian musicology is characterized by the substantial expansion of the spheres and directions of the researches. The enormous layer of the phenomenon that was not examined by the musical art during the Soviet epoch is actual today. The question is about the pop and jazz performance that tested the stormy splash of the development from the beginning of 1990th and today tested numeral influences and acquired the most various forms. During the time of the Ukraine independence «pop» and «jazz» directions of researches began and acquired the development in the Ukrainian musicology. Vadym Olendarov who analysed jazz of the Soviet period and Volodymyr Romanko who analysed jazz art as the part of the Ukrainian culture became its founders. Different directions of the researches destroy its understanding on the culturological level.
The pop-jazz vocal performance as a subject of contemporary musicological researches in Ukraine
Keywords: естрадно-джазове вокальне виконавство; дисертаційне дослідження; українське музикознавство; pop and jazz vocal performances; dissertation research; Ukrainian musicology